Essential Oils as an Antifungal Alternative to Control Several Species of Fungi Isolated from Musa paradisiaca: Part III - Maritza D. Ruiz Medina; Jenny Ruales (Microorganisms)
Essential oils (EOs) are widely recognized for their antifungal properties, but their efficacy against specific phytopathogenic fungi associated with banana (Musa paradisiaca) rot remains underexplored. This study aimed to evaluate the antifungal potential of EOs from Origanum vulgare, Salvia rosmarinus, Syzygium aromaticum, Thymus vulgaris, Cinnamomum verum, and Ocimum basilicum against five fungal species isolated from infected banana peels. Fungal isolates were obtained using PDA medium supplemented with chloramphenicol and were purified by weekly subculturing. Morphological and microscopic characterization was complemented by molecular identification based on ITS sequencing and phylogenetic reconstruction using Neighbor-Joining and UPGMA methods in MEGA v11. In vitro and ex vivo antifungal assays were performed at EO concentrations ranging from 200 to 1000 ppm. Thyme oil exhibited the strongest inhibitory effect, with complete growth suppression at 1000 ppm. Cinnamon and oregano also demonstrated effective inhibition at 600 ppm, while clove, rosemary, and basil were markedly less effective. Statistical analysis confirmed significant effects of EO type and concentration on fungal growth (p < 0.001). Molecular results showed strong phylogenetic support for isolate identification, with bootstrap values above 93% in most clades. These findings support the selective use of specific EOs as sustainable alternatives to synthetic fungicides in the postharvest management of banana diseases and provide a molecularly supported basis for their targeted application in integrated control strategies.